Environmental gradients drive convergence in life history strategies among disparate but coevolved taxonomic groups - Carla L. Atkinson; Alex J. Franzen; Garrett W. Hopper; Jonathan W. Lopez; Zachery D. Zbinden; Caryn C. Vaughn (Ecology, 2025)
Trait‐based approaches can improve ecological understanding by linking fitness to the environment. The trilateral life history model is an expansion of r‐ and K‐selection theory that reflects trade‐offs between juvenile survival, fecundity, and generation time and describes differential survival of species across environmental gradients. We used this framework to generate and test hypotheses regarding community assembly and the validity of such a model in two disparate taxonomic groups, freshwater mussels and fish. We assessed the distribution of mussel and fish life history strategies across 80 sites spanning aspects of the river continuum concept within the Ouachita Highlands (USA) and asked if their distributions are predicted by a similar life history strategy framework. Because mussel and fish assemblages should both be structured by selective forces in an up‐ to downstream trajectory, we expected both taxa to converge on more species‐rich assemblages with a greater proportion of equilibrium strategists in larger, more stable downstream habitats. We found that both mussel and fish species richness increased with watershed area as well as the proportion of equilibrium strategists in the assemblages. Our study validates the use of the trilateral life history model to test hypotheses about the distribution patterns of two coevolved taxonomic groups.

A camera based method for assessing surf amenity of submerged nearshore structures in a wave basin by quantifying wave breaking - Michael E. Thompson; Alex Atkinson; Evan Watterson; Nick Naderi; Heiko Loehr; Tom E. Baldock (Ocean Engineering, 2023)

Correction to: Experimental determination of the temperature dependence of oxygen-isotope fractionation between water and chitinous head capsules of chironomid larvae - Alex Lombino; Tim Atkinson; Stephen J. Brooks; Darren R. Gröcke; Jonathan Holmes; Vivienne J. Jones; Jim D. Marshall (Journal of Paleolimnology, 2021)

Experimental determination of the temperature dependence of oxygen-isotope fractionation between water and chitinous head capsules of chironomid larvae - Alex Lombino; Tim Atkinson; Stephen J. Brooks; Darren R. Gröcke; Jonathan Holmes; Vivienne J. Jones; Jim D. Marshall (Journal of Paleolimnology, 2021)
Oxygen-isotope values of invertebrate cuticle preserved in lake sediments have been used in palaeoenvironmental reconstructions, generally with the assumption that fractionation of oxygen isotopes between cuticle and water ( $$\upalpha_{\text{cuticle}-\text{H}_{2}\text{O}}$$ α cuticle - H 2 O ) is independent of temperature. We cultured chironomid larvae in the laboratory with labelled oxygen-isotope water and across a range of closely controlled temperatures from 5 to 25 °C in order to test the hypothesis that fractionation of oxygen isotopes between chironomid head capsules and water ( $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O ) is independent of temperature. Results indicate that the hypothesis can be rejected, and that $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O decreases with increasing temperature. The scatter in the data suggests that further experiments are needed to verify the relationship. However, these results indicate that temperature-dependence of $$\upalpha_{\text{chironomid}-\text{H}_{2}\text{O}}$$ α chironomid - H 2 O should be considered when chironomid δ 18 O is used as a paleoenvironmental proxy, especially in cases where data from chironomids are combined with oxygen-isotope values from other materials for which fractionation is temperature dependent, such as calcite, in order to derive reconstructions of past water temperature.

Lifeform indicators reveal large‐scale shifts in plankton across the North‐West European shelf - Jacob Bedford; Clare Ostle; David G. Johns; Angus Atkinson; Mike Best; Eileen Bresnan; Margarita Machairopoulou; Carolyn A. Graves; Michelle Devlin; Alex Milligan; Sophie Pitois; Adam Mellor; et al. (Global Change Biology, 2020)
Increasing direct human pressures on the marine environment, coupled with climate‐driven changes, is a concern to marine ecosystems globally. This requires the development and monitoring of ecosystem indicators for effective management and adaptation planning. Plankton lifeforms (broad functional groups) are sensitive indicators of marine environmental change and can provide a simplified view of plankton biodiversity, building an understanding of change in lower trophic levels. Here, we visualize regional‐scale multi‐decadal trends in six key plankton lifeforms as well as their correlative relationships with sea surface temperature (SST). For the first time, we collate trends across multiple disparate surveys, comparing the spatially and temporally extensive Continuous Plankton Recorder (CPR) survey (offshore) with multiple long‐term fixed station‐based time‐series (inshore) from around the UK coastline. These analyses of plankton lifeforms showed profound long‐term changes, which were coherent across large spatial scales. For example, ‘diatom’ and ‘meroplankton’ lifeforms showed strong alignment between surveys and coherent regional‐scale trends, with the 1998–2017 decadal average abundance of meroplankton being 2.3 times that of 1958–1967 for CPR samples in the North Sea. This major, shelf‐wide increase in meroplankton correlated with increasing SSTs, and contrasted with a general decrease in holoplankton (dominated by small copepods), indicating a changing balance of benthic and pelagic fauna. Likewise, inshore‐offshore gradients in dinoflagellate trends, with contemporary increases inshore contrasting with multi‐decadal decreases offshore (approx. 75% lower decadal mean abundance), urgently require the identification of causal mechanisms. Our lifeform approach allows the collation of many different data types and time‐series across the NW European shelf, providing a crucial evidence base for informing ecosystem‐based management, and the development of regional adaptation plans.

Mapping paddy rice fields by applying machine learning algorithms to multi-temporal Sentinel-1A and Landsat data - Alex O. Onojeghuo; George A. Blackburn; Qunming Wang; Peter M. Atkinson; Daniel Kindred; Yuxin Miao (International Journal of Remote Sensing, 2018)

The phylogeographical clade trade: tracing the impact of human‐mediated dispersal on the colonization of northern Europe by the oak gallwasp Andricus kollari - GRAHAM N. STONE; RICHARD J. CHALLIS; RACHEL J. ATKINSON; GYÖRGY CSÓKA; ALEX HAYWARD; GEORGE MELIKA; SERAP MUTUN; SONJA PREUSS; ANTONIS ROKAS; EBRAHIM SADEGHI; KARSTEN SCHÖNROGGE (Molecular Ecology, 2007)
Human dispersal of organisms is an important process modifying natural patterns of biodiversity. Such dispersal generates new patterns of genetic diversity that overlie natural phylogeographical signatures, allowing discrimination between alternative dispersal mechanisms. Here we use allele frequency and DNA sequence data to distinguish between alternative scenarios (unassisted range expansion and long range introduction) for the colonization of northern Europe by an oak‐feeding gallwasp, Andricus kollari . Native to Mediterranean latitudes from Portugal to Iran, this species became established in northern Europe following human introduction of a host plant, the Turkey oak Quercus cerris . Colonization of northern Europe is possible through three alternative routes: (i) unassisted range expansion from natural populations in the Iberian Peninsula; (ii) unassisted range expansion from natural populations in Italy and Hungary; or (iii) descent from populations imported to the UK as trade goods from the eastern Mediterranean in the 1830s. We show that while populations in France were colonized from sources in Italy and Hungary, populations in the UK and neighbouring parts of coastal northern Europe encompass allozyme and sequence variation absent from the known native range. Further, these populations show demographic signatures expected for large stable populations, rather than signatures of rapid population growth from small numbers of founders. The extent and spatial distribution of genetic diversity in the UK suggests that these A. kollari populations are derived from introductions of large numbers of individuals from each of two genetically divergent centres of diversity in the eastern Mediterranean. The strong spatial patterning in genetic diversity observed between different regions of northern Europe, and between sites in the UK, is compatible with leptokurtic models of population establishment.